Knowledge, Attitude, and Practice Regarding Child Abuse and Neglect among Dental Practitioners - Rachana . P. B1 , Supriya H2 , Seema M3, Vijaya Lakshmi G4 , Meghashree Kerpala5 , Charisma Thimmaia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Child abuse and neglect (CAN) is a prevalent and growing public health problem. Dentistsare in a strategic position to identify and report cases of CAN as common signs of child abuse are in theorofacial region. Proper knowledge and awareness are required for early identification and intervention toprevent untoward consequences.Methodology: A cross-sectional observational study using a predesigned three parts questionnaire wasconducted among general and specialty practitioners in branches of dentistry of Dakshina Kannada district,Karnataka to assess the knowledge, awareness, and behavioral practice towards child abuse and neglect. Thedata extracted were tabulated, statistically analyzed and results calculated based on percentages using SPSS.Result: The participants in the current study demonstrated sufficient knowledge of the signs and symptomsof child physical abuse, actions that should be taken in suspected cases, circumstances in which to reportsuch cases, and the legal authorities to which they should be reported. Most of the participants desired forfurther training such as courses or workshops on examining, diagnosing, and reporting cases of child abuse.Conclusion: - The study suggests that dental practitioners need an effective education to increase theirknowledge and awareness on CAN for its precocious identification and diagnosis as an assay for earlyintervention.